2023
DOI: 10.1002/anie.202315861
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Early Atherosclerotic Plaques Using a Sequence‐Activated Fluorescence Probe for the Simultaneous Detection of γ‐Glutamyl Transpeptidase and Hypobromous Acid

Hui Wang,
Xiaoting Zhang,
Ping Li
et al.

Abstract: Atherosclerosis is a lipoprotein‐driven disease, and there is no effective therapy to reverse atherosclerosis or existing plaques. Therefore, it is urgently necessary to create a noninvasive and reliable approach for early atherosclerosis detection to prevent initial plaque formation. Atherosclerosis is intimately associated with inflammation, which is accompanied by an excess of reactive oxygen species (ROS), leading to cells requiring more glutathione (GSH) to resist severe oxidative stress. Therefore, the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Increased γ-GGT activity indicates an insufficient antioxidant capacity and induces oxidative stress. Given its association with oxidative stress, γ-GGT has been recognized as a sensitive and reliable marker of cellular damage and stress response [ 14 , 15 ].Beyond its role in oxidative stress, γ-GGT has also been implicated in inflammatory processes, endothelial dysfunction, and atherosclerosis [ 6 , 16 , 17 ]. This association is particularly relevant in the context of PD, where chronic inflammation and oxidative stress are key factors contributing to the pathogenesis of associated comorbidities [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased γ-GGT activity indicates an insufficient antioxidant capacity and induces oxidative stress. Given its association with oxidative stress, γ-GGT has been recognized as a sensitive and reliable marker of cellular damage and stress response [ 14 , 15 ].Beyond its role in oxidative stress, γ-GGT has also been implicated in inflammatory processes, endothelial dysfunction, and atherosclerosis [ 6 , 16 , 17 ]. This association is particularly relevant in the context of PD, where chronic inflammation and oxidative stress are key factors contributing to the pathogenesis of associated comorbidities [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is yet unclear how γ-GGT affects prognosis in the dialysis population. Increased γ-GGT levels have been linked to CV risk, infection-related and all-cause mortality, as well as CV hospitalization in hemodialysis patients, according to a prior study [ 17 ]. In this retrospective study, we analyzed 640 PD patients from a single center and observed that in the two categories of γ-GGT median values across both sexes, those with lower levels of γ-GGT exhibited significantly lower all-cause and cardiovascular mortality rates at one, three, and five years.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group successfully developed a sequence-activated fluorescent probe for the detection of GGT and HOBr . However, the variations in emission channels of the probe following reaction with analytes were modest (not exceeding 60 nm), which could potentially result in noticeable fluorescence crosstalk.…”
mentioning
confidence: 99%